Repression of Noxa by Bmi1 contributes to deguelin‐induced apoptosis in non‐small cell lung cancer cells. Issue 12 (25th September 2018) - Li, Wei; Yu, Xinfang; Xia, Zhenkun; Yu, Xinyou; Xie, Li; Ma, Xiaolong; Zhou, Huiling; Liu, Lijun; Wang, Jian; Yang, Yifeng; Liu, Haidan
Abstract: Deguelin, a natural rotenoid isolated from several plants, has been reported to exert anti‐tumour effects in various cancers. However, the molecular mechanism of this regulation remains to be fully elucidated. Here, we found that deguelin inhibited the growth of non‐small cell lung cancer (NSCLC) cells both in vitro and in vivo by downregulation of Bmi1 expression. Our data showed that Bmi1 is highly expressed in human NSCLC tissues and cell lines. Knockdown of Bmi1 significantly suppressed NSCLC cell proliferation and colony formation. Deguelin treatment attenuated the binding activity of Bmi1 to the Noxa promoter, thus resulting in Noxa transcription and apoptosis activation. Knockdown of Bmi1 promoted Noxa expression and enhanced deguelin‐induced apoptosis, whereas overexpression of Bmi1 down‐regulated Noxa protein level and deguelin‐induced apoptosis. Overall, our study demonstrated a novel apoptotic mechanism for deguelin to exert its anti‐tumour activity in NSCLC cells.